(untitled) (UNED Research Journal, 2019)
Introduction: Heavy metal contamination of aquatic ecosystems has been a serious concern throughout the world for many decades, and has caused devastating effects on aquatic organisms. Objective: To evaluate the levels of Cu, Zn, Fe, Pb and Cd in the kidneys of scaly (T. zillii, M. rume and R. ocellatus) and non-scaly (C. gariepinus, Ch. nigrodigitatus and S. filamentosus) fishes in Epe lagoon, Nigeria to understanding the bioaccumulation potential of the kidney relative to other organs in fish that have previously been reported in literature. Methods: We studied concentrations of copper (Cu), iron (Fe), zinc (Zn), cadmium (Cd) and lead (Pb) in the kidneys of 141 scaly fishes (Mo. rume, R. occellatus, T. zillii) and 134 non-scaly fishes (C. gariepinus, S.filamentosus, Ch. nigrodigitatus) and water samples obtained from Epe Lagoon using Standard Atomic Absorption Spectrometry methods. Results: The kidneys of R. ocellatus had the highest levels of Fe (2,92±0,10) and Cd (0,18±0,03), while that of Ch. nigrodigitatus (2,78±0,02) and T. zillii (0,31±0,02) had the lowest concentration of Fe and Cd respectively. T. zillii and M. rume accumulated Cu and Zn in their kidneys respectively more than the others. There was no significant difference (p<0,05) in mean trace metal concentrations among the scaly and non-scaly fishes. The concentrations of metals in fish specimens were below the FEPA and WHO prescribed maximum allowable limits in food fish. Dissolved oxygen (9,0±0,02) and total alkalinity (24,0±0,01) were above FEPA values (dissolved oxygen: 3,0-5,0mg/L and total alkalinity: 3,05-5,3mg/L). The ranking of heavy metals distribution in the water body was Cu (4,70)>Fe (0,72)>Zn (0,13)>Pb (0,007)>Cd (0,006). Bioconcentration factor of Zn was generally high in all species. Conclusion: Close monitoring of these metals in the fishes and the lagoon is important to ensure the safety of fish consumers in the area.